PENGARUH SISTEM INFORMASI MANAJEMEN TERHADAP KINERJA GURU DI MADRASAH ALIYAH NAHDLATUL ULAMA TASIKMALAYA - Sena, Sena; Komalasari, Imas; Luthfiah Resnasari, Upi (STAI Ma'had Aly Al-Hikam Malang, 2023)
In this digital era, many jobs use management information systems, especially in terms of education. Teachers must be able to balance between technology and education. But now there are still many teachers who are minimal in using technology. This study aims to determine the effect of management information systems on teacher performance at Madrasah Aliyah Nahdlatul Ulama Tasikmalaya. The method in this study is a survey method with a quantitative approach that is descriptive and associative. The number of samples is 25 respondents. For the technique of analysis the data used regression. The results showed that there was a positive and significant relationship between management information systems (X) and teacher performance (Y) at Madrasah Aliyah Nahdlatul Ulama Tasikmalaya. This is evidenced by the r count of 0.866 while the r table at a significant level of 5% is 0.404. This means that the hypothesis is accepted that there is a significant positive effect of management information systems (X) on teacher performance (Y). While the calculation results of the coefficient of determination is 74.9%. This means that the management information system contributes 74.9% to teacher performance and 25.1% is influenced by other variables not examined in this study.